Students’ perception on TPACK practices on online language classes in the midst of pandemic - Daniel Ginting; Fahmi Fahmi; Yusawinur Barella; Muhamad Hasbi; Kadnawi Kadnawi; Ahmad Ridho Rojabi; Ainu Zumrudiana (Institute of Advanced Engineering and Science, 2022)
This study investigated technological pedagogical and content knowledge (TPACK) practices during the current COVID-19 pandemic and examined factors influencing students’ perceptions of effective online learning. This study gathered the primary data from 90 university students from four study programs via the online questionnaire. Using an analysis of variance (ANOVA) statistical tool for data analysis, this study found that students’ perceptions of their teachers’ teaching performance in the fully online programs are not significantly different across four study programs. This finding implies that regardless of their study programs, the students had expected that teachers should pay attention to some vital aspects in online learning: using the same learning management system (LMS) for all study programs, and preparing designing practical online modules, taking care of the organization of teaching inputs that promote students’ critical thinking, delivering various teaching inputs and methods, intensifying teachers’ presence in monitoring students’ learning progress, motivating students to learn, and promoting teacher-student mutual respect through effective communication. This study also revealed that teachers play a pivotal role in achieving effective online learning during the pandemic.